2002
DOI: 10.1046/j.1365-2249.2002.01700.x
|View full text |Cite
|
Sign up to set email alerts
|

B7-1 and B7-2 co-stimulatory molecules are required for mercury-induced autoimmunity

Abstract: B7‐1 (CD80) and B7‐2 (CD86) molecules on antigen presenting cells play important roles in providing co‐stimulatory signals required for activation and expansion of autoreactive T cells. Moreover, some reports have suggested that these molecules may have distinct functions in the differentiation of Th1 and Th2 cells. Mercury‐induced autoimmunity in H‐2s mice is characterized by lymphoproliferation of T and B cells, serum increases in IgG1 and IgE and production of antinucleolar antibodies (ANoA). The mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
(63 reference statements)
2
18
0
1
Order By: Relevance
“…We have previously observed that in the GVHD model used here, chronic GVHD can be converted to acute GVHD by the administration of agents that promote T H 1 cytokine responses, for example, administration of recombinant interleukin 12 (Via et al 1994), or by highly selective costimulatory blockade in which the down-regulatory signal delivered by CTLA4 through its preferential ligand CD80 is inhibited (Lang et al 2002). Because both CD80 and CD86 appear to be required for HgIA (Bagenstose et al 2002), we are currently investigating whether low-dose iHg preexposure promotes T H 1 cytokine production and/or interferes with CTLA4-CD80 expression or ligand binding.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously observed that in the GVHD model used here, chronic GVHD can be converted to acute GVHD by the administration of agents that promote T H 1 cytokine responses, for example, administration of recombinant interleukin 12 (Via et al 1994), or by highly selective costimulatory blockade in which the down-regulatory signal delivered by CTLA4 through its preferential ligand CD80 is inhibited (Lang et al 2002). Because both CD80 and CD86 appear to be required for HgIA (Bagenstose et al 2002), we are currently investigating whether low-dose iHg preexposure promotes T H 1 cytokine production and/or interferes with CTLA4-CD80 expression or ligand binding.…”
Section: Discussionmentioning
confidence: 96%
“…The role of B7 molecules in mHgIA has been examined using anti-B7-1 and anti-B7-2 Abs. Treatment with both Abs combined suppressed both short-and long-term mercury-induced hypergammaglobulinemia and ANoA (23). If mercury exposure was of brief duration anti-B7-1 Abs inhibited, while anti-B7-2 delayed ANoA production; however, these effects could be overcome by prolonged mercury exposure (23).…”
Section: Discussionmentioning
confidence: 96%
“…Significantly, exposure of lupusprone mice to low doses of mercury exacerbates idiopathic disease (21), suggesting that idiopathic lupus and mHgIA may share common pathogenic mechanisms. Analogous with idiopathic lupus mHgIA can be suppressed by anti-CD40 ligand (CD40L) Ab or CTLA-4 Ig (22), or a combination of anti-B7-1 (CD80) and anti-B7.2 (CD86) Abs (23). Individually, anti-CD86 Ab suppressed anti-nucleolar autoantibodies (ANoA) and reduced IgE but anti-CD80 Ab was only able to partially reduce the ANoA response (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that CD80 and CD86 can influence the immune response to immunogens by stimulating differentiation of CD4 + T cells into Th1 and Th2 lineages [23,24]. However, it remains highly controversial whether CD80 and CD86 possess distinct roles in the differentiation and regulation of Th1 and Th2 cells [25].…”
Section: Introductionmentioning
confidence: 99%